Shedding Light on the Formation of Stars and Planets: Numerical Simulations with Radiative Transfer - Rogers, Patrick D. (My University, 2012)
We use numerical simulations to examine the fragmentation of protostellar discs via gravitational instability (GI), a proposed formation mechanism for gas-giant planets and brown dwarfs. To accurately model heating and cooling, we have implemented radiative transfer (RT) in the TreeSPH code Gasoline, using the flux-limited diffusion approximation coupled to photosphere boundary cooling. We present 3D radiation hydrodynamics simulations of discs that are gravitationally unstable in the inner 40 AU; these discs do not fragment because the cooling times are too long. In prior work, one of these discs was found to fragment; however, we demonstrate that this resulted from an over-estimate of the photosphere cooling rate. Fragmentation via GI does not appear to be a viable formation mechanism in the inner 40 AU.
We also present simulations of GI in the outer regions of discs, near 100 AU, where we find GI to be a viable formation mechanism. We give a detailed framework that explains the link between cooling and fragmentation: spiral arms grow on a scale determined by the linear gravitational instability, have a characteristic width determined by the balance of heating and cooling, and fragment if this width is less than twice their Hill radius. This framework is consistent with the fragmentation and initial fragment masses observed in our simulations. We apply the framework to discs modelled with the commonly-used beta-prescription cooling and calculate the critical cooling rate for the first time, with results that are consistent with previous estimates measured from numerical experiments.
RT is fundamentally important in the star formation process. Non-ionizing radiation heats the gas and prevents small-scale fragmentation. Ionizing radiation from massive stars is an important feedback mechanism and may disrupt giant molecular clouds. We present methods and tests for our implementation of ionizing radiation, using the Optically-Thin Variable Eddington Tensor method.
Keywords: Planet Formation; Protostellar Discs; Brown Dwarfs; Star Formation; Numerical Simulations; Radiative Transfer; Other Astrophysics and Astronomy; Other Astrophysics and Astronomy